[Certein places gathered out of .S. Austens boke intituled de essentia diuinitatis,] verye necessary to vnderstand certein darke places of the byble and especiallye the Prophetes gachered [sic] by Herman Bodius a faithfull preacher. and now lately turned into Inglysh.] [electronic resource] :
Summary goes here